Solution‐Processed Ternary Oxides as Carrier Transport/Injection Layers in Optoelectronics. Issue 13 (1st July 2019) - Huang, Zhanfeng; Ouyang, Dan; Shih, Chun‐Jen; Yang, Boping; Choy, Wallace C. H.
Abstract: With the remarkable progress in solution‐processed optoelectronics, high performance is required of the carrier transport/injection layer. Ternary oxides containing a variety of crystal structures, and adjustable composition that results in tunable optical and electrical properties, are one of the promising class of candidates to fulfill the requirements of carrier transport/injection layers for high‐performance and stable optoelectronic devices. Solution‐processed ternary oxides have seen considerable progress in recent decades, due to their advantages in the quest to design low‐cost, high‐performance, large‐scale, and stable optoelectronic devices. Herein, the recent advances of solution‐processed ternary oxides are reviewed. The first section consists of a brief introduction to the topic. In the following section, the fundamentals of the effect of tuning ternary oxide composition are summarized. Section three briefly reviews the synthesis approaches for preparing ternary oxides. Section four discusses the recent progress of solution‐processed ternary oxide as carrier transport/injection layer in optoelectronic devices (such as organic solar cells, perovskite solar cells, organic light emitting diodes, etc.). In this section, the impact of controlling ternary oxide composition on device performance and stability is highlighted. Finally, a brief summary and an outlook are given. Abstract : Solution‐processed ternary oxides exhibit tunable optical and electrical properties in carrier transport layers for optoelectronic applications. Many ternary oxides have been developed with desirable properties to cater to various photoactive materials. In this review, the impacts of composition tuning in ternary oxide on achieving high‐performance and stable organic and perovskite optoelectronic devices are summarized.